Deep brain stimulation in post‐traumatic dystonia: A case series study. (29th April 2019) - Li, Hong‐Xia; He, Lu; Zhang, Chen‐Cheng; Eisinger, Robert; Pan, Yi‐Xin; Wang, Tao; Sun, Bo‐Min; Wu, Yi‐Wen; Li, Dian‐You
Abstract: Aims: Deep brain stimulation (DBS) has been proposed as an effective treatment for drug‐intolerant isolated dystonia, but whether it is also efficacious for posttraumatic dystonia (PTD) is unknown. Reports are few in number and have reached controversial conclusions regarding the efficacy of DBS for PTD treatment. Here, we report a case series of five PTD patients with improved clinical benefit following DBS treatment. Methods: Five patients with disabling PTD underwent DBS therapy. The clinical outcomes were assessed with the Burke–Fahn–Marsden dystonia rating scale (BFMDRS) at baseline and the last follow‐up visit (at more than 12 months). Results: Patients 1 and 3 received unilateral globus pallidus internus (GPi) DBS for contralateral dystonia. The subthalamic nucleus (STN) was chosen as target for patients 2 and 4, due to a lesion located in the globus pallidus. Patient 5 had an electrode in the ventral intermediate nucleus (VIM) for treating predominant tremor of left upper extremity, with unexpected improvement of focal hand dystonia. The scores of BFMDRS movement exhibited favorable improvement in all five patients at the last follow‐up, ranging from 52.4% to 78.6%. Conclusions: Deep brain stimulation may be an effective and safe treatment for medically refractory PTD, but this needs to be confirmed by further studies.